RESPONS PERTUMBUHAN IKAN LELE SANGKURIANG (Clarias gariepinus) YANG DIBERI PAKAN BUATAN BERBASIS LIMBAH SAYURAN - Sarmada Sarmada; Rini Marlida; Rina Iskandar (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The aim of this study was to determine the growth response Lele Sangkuriang (Clarias gariepinus ) fed vegetable waste based artificial maintained with different densities. The analysis shows that different stocking solid significantly affect the growth of the test fish .Results of further tests with the Last Significant Diferent ( LSD ) showed treatment A is not significantly different from treatment with B, but treatmen A significantly different with C. Treatment B did not differ significantly with treatment C. The survival rate in the test fish treatment A ( 88.67 % ) , B ( 89.67 % ) C ( 91.56 % ) . Results of the analysis showed that different stocking Solid did not significantly affect the survival rate of the test fish. The value of the test fish feed convention ranged from 1.53 to 1.67. the range of temperature and pH on -site maintenance is in the range appropriate for the test fish